HUBUNGAN TERPAAN INFORMASI TENTANG ETIKA DIGITAL DAN KOMPETENSI DIGITAL TERHADAP PERILAKU BERMEDIA SOSIAL - Hanan Hauzan, Muhammad; Naryoso, Agus; Setyabudi, Djoko (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This study aims to identify and explain the relationship between exposure to information on digital ethics and digital competence on social media behavior. The method used is a quantitative explanatory approach with a population of individuals participating in the